1860
DOI: 10.1111/j.1096-3642.1860.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

XIII. On certain Sensory Organs in Insects, hitherto undescribed*.

Abstract: Read May 3rd, 1860 Jt.. BEFORE proceeding to the details of the following communication, it will be well to remind this Society of the structures I have already pointed out as existing in the Insect tribes, the consideration of which will serve to explain the nature of the new organs about to be described. I n a paper read before the Linnean Society on the 17th June, lS56+, I called attention to groups of hemispherical vesicles, disposed in rows, very regularly arranged, situated at the base of the hccltems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1914
1914
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The form of the invagination was not described by Stange et al [26], Song et al [30], Bogner [39], or Stange [40]; or was erroneously reported as bottle-shaped by Kent et al [23], Chen & Hua [29], and Zhao et al [27]. For this purpose, we consider as a bottle-shaped form only the cases of the unidentified geometrid reported by Hicks [2]; "Pieris sp. ", probably P. rapae or P. brassicae [4]; and F. ryphea (Fig 14).…”
Section: Morphological Patternsmentioning
confidence: 98%
See 4 more Smart Citations
“…The form of the invagination was not described by Stange et al [26], Song et al [30], Bogner [39], or Stange [40]; or was erroneously reported as bottle-shaped by Kent et al [23], Chen & Hua [29], and Zhao et al [27]. For this purpose, we consider as a bottle-shaped form only the cases of the unidentified geometrid reported by Hicks [2]; "Pieris sp. ", probably P. rapae or P. brassicae [4]; and F. ryphea (Fig 14).…”
Section: Morphological Patternsmentioning
confidence: 98%
“…If the bottom of the atrium is rounded, then the form is drop-shaped, as in Morpho helenor achillaena (Fig 16). Tubular vom Rath's organs have more or less the same width from the opening to the bottom of the cavity, so they do not form an atrium; examples are Argynnis paphia (Nymphalidae: Heliconiinae) [2] and Cactoblastis cactorum (Pyralidae) [26]. Finally, tapered vom Rath's organs have an opening wider than the bottom of the cavity, forming a funnel, but not an atrium, as in Helicoverpa armigera [27] and Mythimna separata (Noctuidae) [28].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations